IMPLEMENTASI AUDIT BERBASIS RESIKO DAN DUE PROFESIONAL CARE YANG DIMILIKI AUDITOR BERDAMPAK PADA KUALITAS AUDIT - Surtikanti, Surtikanti; Saleh, Dean Subhan (Jurnal Riset Akuntansi, 2019)
ABSTRACT Due professional care and work experience are the most important to be have by auditor. The auditor must have due professional care and work experience to produce a good financial report. If auditor have a good due professional care and work experience, then the quality of audit will be good. Due professional care and work experience will affect the quality of audit. But in fact, the quality of audit produced bay auditor is not good enough. The purpose of this research is the effect of due professional care and work experienceto quality of audit survey on KAP existing in Bandung. The method used in this research is descriptive method, verification with quantitative approach. Descriptive method used to determine due professional care and work experience to quality of audit. The test statistic used is the calculation of validity and relibility testing using software SPSS 18.0 for windows. For verification method using SEM PLS, evaluation results outer model by value loading factor and discrimination validity. All the indicators used in this research is valid and able to measure latent variables. The result from this research indicate that due professional care has a significant impact on the quality of audit that if due professional care great then the resulting quality of audit would be great, while work experience has a significant impact on the quality of audit that if work experience is good then the quality of audit would be good. Keywords : Due Professional Care, Risk Audit, and Quality of Audit